(untitled) (Global Journal of Human-Social Science, 2024)
This article is part of a master s thesis that aims to present an adaptation to the Ross-Heidecke model for calculating building depreciation In addition to including the obsolescence coefficient the adaptation of the conservation coefficient is proposed based on parameterization from the Dutch standard for building inspection The proposed method is applied in hypothetical cases where levels of conservation obsolescence and useful life can be evaluated under extreme situations The inclusion of the obsolescence coefficient for determining building depreciation is essential as it assists in developing a more accurate assessment resulting in a reduction of subjectivity